2008
DOI: 10.1111/j.1755-148x.2007.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of Nrf2 pathway in (photo)‐oxidative stress response in melanocytes and keratinocytes of the human epidermis

Abstract: The expression of genes encoding antioxidant and/or phase 2 detoxifying enzymes can be enhanced in response to various environmental stresses. The main transcription factor involved in this response is nuclear factor erythroid 2-related factor 2 (Nrf2). Nrf2 activity is negatively regulated by the protein Kelch-like-Ech-associated-protein 1 (Keap1). While the roles of Nrf2 and phase 2 genes in chemoprevention of carcinogenesis have been well described; only few studies have dealt with their role in skin cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
118
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 46 publications
6
118
0
Order By: Relevance
“…The effect was moderately greater after exposure to UVA than solar light. 53) A previous study showed an induction of HO-1 mRNA expression in hairless mice at several time points following UVA treatment (38.7 J/cm 2 ). No mRNA was observed in animals exposed to UVB (0.550 mJ/cm 2 ).…”
Section: Discussionmentioning
confidence: 93%
“…The effect was moderately greater after exposure to UVA than solar light. 53) A previous study showed an induction of HO-1 mRNA expression in hairless mice at several time points following UVA treatment (38.7 J/cm 2 ). No mRNA was observed in animals exposed to UVB (0.550 mJ/cm 2 ).…”
Section: Discussionmentioning
confidence: 93%
“…Physiological doses of UVB, in contrast, did not activate Nrf2 in primary mouse keratinocytes or in murine back skin epidermis (Durchdewald et al 2007). Recent results even indicated repression of Nrf2 activity by high UVB doses in normal human keratinocytes (Marrot et al 2008;Kokot et al 2009). The basal activity of Nrf2 seems to be required for protection of keratinocytes from UV cytotoxicity, since Nrf2 knockout mice showed a higher rate of apoptosis and oxidative damage in ear skin keratinocytes after UVB irradiation (Kawachi et al 2008).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that increased Nrf2 mRNA expression occurs due to UVA-induced oxidative stress (37,38). Additionally, Marrot et al (39) elucidated that UVA radiation promotes the expression of phase2 enzymes, particularly heme oxygenase 1, in keratinocytes. These phase 2 enzymes are the main method by which cells inhibit ROS generation.…”
Section: Discussionmentioning
confidence: 99%